The Influence Of Transformational Leadership Style, Compensation, And Working Environment Employee Loyalty At Pt Pradipta Bhumi Construction - Epsilandri Septyarini; Tri Ratna Purnamarini; Yoga Zulfika (UNIVED Press, 2024)
This research aims to test whether transformational leadership style, compensation and work environment influence employee loyalty at PT. Pradipta Bhumi Construction. This research took samples from employees of PT. Pradipta Bhumi Construction. The sampling method is nonprobability sampling with a purposive sampling method. Data collection was carried out using a questionnaire distributed directly to employees at PT. Pradipta Bhumi Construction. The number of questionnaires processed was 50 questionnaires obtained from PT employees. Pradipta Bhumi Construction. This research data was analyzed using multiple linear regression analysis and this processing was carried out using the SPSS version 26 application. The results of this research show that all independent variables can partially or simultaneously influence the dependent variable. The variables Transformational Leadership Style, Compensation, and Work Environment, individually or jointly, influence employee loyalty.